Animal inflammation-based models of depression and their application to drug discovery. (3rd October 2017) - Ma, Li; Demin, Konstantin A.; Kolesnikova, Tatyana O.; Kharsko, Sergey L.; Zhu, Xiaokang; Yuan, Xiaodong; Song, Cai; Meshalkina, Darya A.; Leonard, Brian E.; Tian, Li; Kalueff, Allan V.
ABSTRACT: Introduction : Depression, anxiety and other affective disorders are globally widespread and severely debilitating human brain diseases. Despite their high prevalence and mental health impact, affective pathogenesis is poorly understood, and often remains recurrent and resistant to treatment. The lack of efficient antidepressants and presently limited conceptual innovation necessitate novel approaches and new drug targets in the field of antidepressant therapy. Areas covered : Herein, the authors discuss the emerging role of neuro-immune interactions in affective pathogenesis, which can become useful targets for CNS drug discovery, including modulating neuroinflammatory pathways to alleviate affective pathogenesis. Expert opinion : Mounting evidence implicates microglia, polyunsaturated fatty acids (PUFAs), glucocorticoids and gut microbiota in both inflammation and depression. It is suggested that novel antidepressants can be developed based on targeting microglia-, PUFAs-, glucocorticoid- and gut microbiota-mediated cellular pathways. In addition, the authors call for a wider application of novel model organisms, such as zebrafish, in studying shared, evolutionarily conserved (and therefore, core) neuro-immune mechanisms of depression.